Marketing Communication Strategy of Wardah Products for Multigenerational Consumers in Medan City - Putri Maharani; Muhammad Alfikri (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
The purpose of this study is to analyze the marketing communication strategy of Wardah products to multigenerational consumers in Medan. The increasingly competitive cosmetics industry demands companies to be able to adjust their marketing communication strategies to the characteristics of multigenerational consumers, starting from Generation X, Millennials, to Generation Z. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, observation, and documentation. Research informants were selected purposively based on their experience using Wardah products and their involvement in receiving the product's marketing communication messages. Data are described through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that Wardah implements an integrated marketing communication strategy through a combination of digital and conventional media. Social media such as Instagram, Tiktok, Facebook, and YouTube are the main means of reaching Generation Z and Millennials through interactive, educational, and creative content, while television advertisements, on-the-go promotions, and interpersonal communication are still effective for Generation X. This study also found that halal image, product safety, and religious values are the main generations that are able to build multi-consumer loyalty. Furthermore, the use of influencers and brand ambassadors has proven effective in increasing brand awareness and strengthening Wardah's brand image amidst the competitive cosmetics industry.